Neuropathological Characterization of a Dravet Syndrome Knock-In Mouse Model Useful for Investigating Cannabinoid Treatments - Satta, Valentina; Alonso, Cristina; Díez, Paula; Martín-Suárez, Soraya; Rubio, Marta; Encinas, Juan M.; Fernández-Ruiz, Javier; Sagredo, Onintza (Frontiers in Molecular Neuroscience, 2021)
Dravet syndrome (DS) is an epileptic syndrome caused by mutations in the Scn1a gene encoding the α1 subunit of the sodium channel Nav1.1, which is associated with febrile seizures that progress to severe tonic-clonic seizures and associated comorbidities. Treatment with cannabidiol has been approved to reduce seizures in DS, but it may also be active against these comorbidities. The aim of this study was to validate a new mouse model of DS having lower mortality than previous models, which may serve to further evaluate therapies for the long-term comorbidities. This new model consists of heterozygous conditional knock-in mice carrying a missense mutation (A1783V) in Scn1a gene expressed exclusively in neurons of the CNS (Syn-Cre/Scn1aWT/A1783V). These mice have been used here to determine the extent and persistence of the behavioral deterioration in different postnatal days (PND), as well as to investigate the alterations that the disease produces in the endocannabinoid system and the contribution of inflammatory events and impaired neurogenesis in the pathology. Syn-Cre/Scn1aWT/A1783V mice showed a strong reduction in hindlimb grasp reflex at PND10, whereas at PND25, they presented spontaneous convulsions and a greater susceptibility to pentylenetetrazole-induced seizures, marked hyperactivity, deficient spatial working memory, lower levels of anxiety, and altered social interaction behavior. These differences disappeared at PND40 and PND60, except the changes in social interaction and anxiety. The analysis of CNS structures associated with these behavioral alterations revealed an elevated glial reactivity in the prefrontal cortex and the dentate gyrus. This was associated in the dentate gyrus with a greater cell proliferation detected with Ki67 immunostaining, whereas double-labeling analyses identified that proliferating cells were GFAP-positive suggesting failed neurogenesis but astrocyte proliferation. The analysis of the endocannabinoid system of Syn-Cre/Scn1aWT/A1783V mice confirmed reductions in CB1 receptors and MAGL and FAAH enzymes, mainly in the cerebellum but also in other areas, whereas CB2 receptors became upregulated in the hippocampus. In conclusion, Syn-Cre/Scn1aWT/A1783V mice showed seizuring susceptibility and several comorbidities (hyperactivity, memory impairment, less anxiety, and altered social behavior), which exhibited a pattern of age expression similar to DS patients. Syn-Cre/Scn1aWT/A1783V mice also exhibited greater glial reactivity and a reactive response in the neurogenic niche, and regional changes in the status of the endocannabinoid signaling, events that could contribute in behavioral impairment.